E-learning in Nepal: Bane or Boon? - Sharma, Pradip (Pragnya Sarathi प्रज्ञा-सारथि, 2025)
The study aims to delve into the Gurukul education system and its shift to e-learning caused by COVID-19 in pedagogical delivery in Nepal, that helps to comply with the world market. E-learning refers to web-based pedagogy that integrates information and communication technology (ICT). It not only helps in delivering quality education but also boosts up digital literacy. The breakthrough in scientific technology has swarmed all fields, including education, so that e-education has become a must to overcome illiteracy and backwardness of the nation. The study probes the evolution of distance learning amid the backwardness and illiteracy of Nepal, which can be outwitted, instrumentalizing computer-based teaching-learning. It also makes use of descriptive hermeneutics of the available literature focused on e-learning to reach the conclusion that online education in the Global South is a boon because it empowers the learners who have been unable to attend face-to-face classes.